Resistance Training with Instability for Patients with Parkinson's Disease - Silva-Batista, Carla; Corcos, Daniel M.; Roschel, Hamilton; Kanegusuku, Helcio; Bucken Gobbi, Lilian Teresa [UNESP]; Pimentel Piemonte, Maria Elisa; Tavares Mattos, Eugenia Casella; De Mello, Marco Tulio; Forjaz, Claudia L. M.; Tricoli, Valmor; Ugrinowitsch, Carlos (Lippincott Williams & Wilkins, 2016)
Purpose: This randomized controlled trial compared the effects of resistance training (RT) and RT with instability (RTI) on the timed up and go test (TUG), on-medication Unified Parkinson's Disease Rating Scale part III motor subscale score (UPDRS-III), Montreal Cognitive Assessment (MoCA) score, Parkinson's Disease Questionnaire (PDQ-39) score, and muscle strength in the leg press exercise (one-repetition maximum) of patients with Parkinson's disease (PD). Methods: Thirty-nine patients with moderate to severe PD were randomly assigned to a nonexercising control group (C), RT group, and RTI group. The RT and RTI groups performed progressive RT twice a week for 12 wk. However, only the RTI group used high motor complexity exercises (i.e., progressive RT with unstable devices), for example, half squat exercise on the BOSU (R) device. The primary outcome was mobility (TUG). The secondary outcomes were on-medication motor signs (UPDRS-III), cognitive impairment (MoCA), quality of life (PDQ-39), and muscle strength (one-repetition maximum). Results: There were no differences between RTI and RT groups for any of the outcomes at posttraining (P > 0.05). However, there were differences between RTI and C groups in the TUG, MoCA, and muscle strength values at posttraining (P<0.05). Only the RTI group improved the TUG (-1.9 s), UPDRS-III score (-4.5 score), MoCA score (6.0 score), and PDQ-39 score (-5.2 score) from pre- to posttraining (P<0.001). Muscle strength improved for both training groups (P < 0.001). No adverse events were reported during the trial. Conclusions: Both training protocols improved muscle strength, but only RTI improved the mobility, motor signs, cognitive impairment, and quality of life, likely because of the usage of high motor complexity exercises. Thus, RTI may be recommended as an innovative adjunct therapeutic intervention for patients with PD.
Keywords: EXERCISE TRAINING; MOTOR COMPLEXITY; MOBILITY; MOTOR SIGNS; COGNITIVE IMPAIRMENT; QUALITY OF LIFE